1098 CHARACTERIZATION OF DIFFERENT TYPES OF LV REMODELING USING QUANTITATIVE INTRACARDIAC FLUID-DYNAMICS. (15th December 2022) - Calvelli, Pierangelo; Sabatino, Jolanda; Bella, Sabrina La; Rosa Romano, Letizia; Strangio, Antonio; Leo, Isabella; Montemurro, Vincenzo; Critelli, Claudia; Maglione, Marco; Troilo, Fabio; Loliva, Giuseppe; Salvo, Giovanni Di; et al.
Abstract: Background: Hyperdoppler is a novel advanced echocardiographic technique for the quantitative assessment of intracardiac fluid-dynamics. Recently, its use has been proven useful to complement traditional echocardiographic evaluation of cardiac function in Heart Failure. However, no specific data are available on its application to differentiate between different types of LV remodeling. Thus, our aim was to investigate whether quantitative changes in fluid dynamics might be able to characterize patients with different ventricular geometry. Methods: We enrolled 100 consecutive patients with one of the following: LV concentric hypertrophy (CH), eccentric hypertrophy (EH), concentric remodeling, normal LV geometry (CTRL). They underwent a complete echocardiographic examination with intracardiac fluid-dynamic analysis by Color Vector Flow Mapping (Hyperdoppler, Esaote, Genova, Italy). The following parameters were obtained: vortex area (VA); vortex length (VL); vortex depth (VD). Bland Altman Plot has been used to assess intra and inter-observer variability. Results: Mean Vortex Depth was significantly higher in CR (p=0.011), CH (p=0.001) and EH (p=0.025) compared to CTRL (p=0.013, p=0.001 and p=0.022, respectively). In addition, CH had significantly higher Vortex Length (p= 0.008) and larger VA (p=0.012) compared to CTRL. No significative differences in vortices parameters have been observed between CH and EH. Conclusion(s): Quantitative fluid-dynamic assessment was feasible and reliable in the whole population and is a promising tool to complement standard echocardiography for the early characterization of different types of LV remodeling.